2014
DOI: 10.1111/bph.12720
|View full text |Cite
|
Sign up to set email alerts
|

Agomelatine: mechanism of action and pharmacological profile in relation to antidepressant properties

Abstract: Agomelatine behaves both as a potent agonist at melatonin MT1 and MT2 receptors and as a neutral antagonist at 5-HT2C receptors. Accumulating evidence in a broad range of experimental procedures supports the notion that the psychotropic effects of agomelatine are due to the synergy between its melatonergic and 5-hydroxytryptaminergic effects. The recent demonstration of the existence of heteromeric complexes of MT1 and MT2 with 5-HT2C receptors at the cellular level may explain how these two properties of agom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
106
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(115 citation statements)
references
References 154 publications
1
106
0
6
Order By: Relevance
“…These studies demonstrated that the effects of acute stress on glutamate efflux in non-stressed control (NSC) rats are fundamentally different compared to responses in rats with a prior stress history and also determined that the effects of stress can be modulated by antidepressant administration Piroli et al, 2013), including the antidepressant agomelatine (Reagan et al, 2012). Agomelatine is a novel antidepressant (de Bodinat et al, 2010;Guardiola-Lemaitre et al, 2014) that acts as a melatonergic (MT1 and MT2) receptor agonist (Audinot et al, 2003) and 5HT 2C antagonist (Millan et al, 2003). Agomelatine produces antidepressant-like effects in various animal models of depression (Papp et al, 2003;Bourin et al, 2004;Barden et al, 2005;Bertaina-Anglade et al, 2006;Paizanis et al, 2010;Rainer et al, 2012;Norman et al, 2012;Schmelting et al, 2013) and anxiety (Millan et al, 2005;Papp et al, 2006) and is an effective antidepressant in patients with MDD (Loo et al, 2002;Kennedy and Emsley, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that the effects of acute stress on glutamate efflux in non-stressed control (NSC) rats are fundamentally different compared to responses in rats with a prior stress history and also determined that the effects of stress can be modulated by antidepressant administration Piroli et al, 2013), including the antidepressant agomelatine (Reagan et al, 2012). Agomelatine is a novel antidepressant (de Bodinat et al, 2010;Guardiola-Lemaitre et al, 2014) that acts as a melatonergic (MT1 and MT2) receptor agonist (Audinot et al, 2003) and 5HT 2C antagonist (Millan et al, 2003). Agomelatine produces antidepressant-like effects in various animal models of depression (Papp et al, 2003;Bourin et al, 2004;Barden et al, 2005;Bertaina-Anglade et al, 2006;Paizanis et al, 2010;Rainer et al, 2012;Norman et al, 2012;Schmelting et al, 2013) and anxiety (Millan et al, 2005;Papp et al, 2006) and is an effective antidepressant in patients with MDD (Loo et al, 2002;Kennedy and Emsley, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Agomelatine, the action of which is based on both MT1/MT2 receptor agonist and 5-HT 2C receptor antagonist properties (Guardiola-Lemaitre et al, 2014), is an effective antidepressant with similar efficacy to standard antidepressants and better tolerability (Taylor et al, 2014). Agomelatine-treated patients are less likely than those receiving other antidepressants to discontinue treatment because of adverse effects (Taylor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Among the different antidepressant compounds, agomelatine is an agonist at melatonergic MT1 and MT2 receptors and a 5-HT 2C receptor antagonist displaying antidepressant and anxiolytic properties in several validated animal models. Agomelatine is also able to modulate neuroplasticity in both basal conditions and in models of depression (see refs 23,24 for review).…”
mentioning
confidence: 99%